Mammalian eukaryotic initiation factor 2 alpha kinases functionally substitute for GCN2 protein kinase in the GCN4 translational control mechanism of yeast. - Dever, T E (1993)
Phosphorylation of the alpha subunit of eukaryotic initiation factor 2 (eIF-2 alpha) in Saccharomyces cerevisiae by the GCN2 protein kinase stimulates the translation of GCN4 mRNA. The protein kinases heme-regulated inhibitor of translation (HRI) and double-stranded RNA-dependent eIF-2 alpha protein kinase (dsRNA-PK) inhibit initiation of translation in mammalian cells by phosphorylating Ser-51 of eIF-2 alpha. We show that HRI and dsRNA-PK phosphorylate yeast eIF-2 alpha in vitro and in vivo and functionally substitute for GCN2 protein to stimulate GCN4 translation in yeast. In addition, high-level expression of either mammalian kinase in yeast decreases the growth rate, a finding analogous to the inhibition of total protein synthesis by these kinases in mammalian cells. Phosphorylation of eIF-2 alpha inhibits initiation in mammalian cells by sequestering eIF-2B, the factor required for exchange of GTP for GDP on eIF-2. Mutations in the GCN3 gene, encoding a subunit of the yeast eIF-2B complex, eliminate the effects of HRI and dsRNA-PK on global and GCN4-specific translation in yeast. These results provide further in vivo evidence that phosphorylation of eIF-2 alpha inhibits translation by impairing eIF-2B function and identify GCN3 as a regulatory subunit of eIF-2B. These results also suggest that GCN4 translational control will be a good model system to study how mammalian eIF-2 alpha kinases are modulated by environmental signals and viral regulatory factors.